Evaluating the Maintenance of Lifestyle Changes in a Randomized Controlled Trial of the ‘Get Healthy, Stay Healthy’ Program - Fjeldsoe, Brianna S (JMIR Mhealth Uhealth, 2016)
BACKGROUND: Extending contact with participants after initial, intensive intervention may support maintenance of weight loss and related behaviors. OBJECTIVE: This community-wide trial evaluated a text message (short message service, SMS)-delivered, extended contact intervention (‘Get Healthy, Stay Healthy’ (GHSH)), which followed on from a population-level, behavioral telephone coaching program. METHODS: This study employed a parallel, randomized controlled trial: GHSH compared with no continued contact (standard practice). Participants (n=228) were recruited after completing a 6-month lifestyle telephone coaching program: mean age = 53.4 (standard deviation (SD)=12.3) years; 66.7% (152/228) female; mean body mass index (BMI) upon entering GHSH=29.5 kg/m2 (SD = 6.0). Participants received tailored text messages over a 6-month period. The message frequency, timing, and content of the messages was based on participant preference, ascertained during two tailoring telephone calls. Primary outcomes of body weight, waist circumference, physical activity (walking, moderate, and vigorous sessions/week), and dietary behaviors (fruit and vegetable serves/day, cups of sweetened drinks per day, takeaway meals per week; fat, fiber and total indices from the Fat and Fiber Behavior Questionnaire) were assessed via self-report before (baseline) and after (6-months) extended contact (with moderate-vigorous physical activity (MVPA) also assessed via accelerometry). RESULTS: Significant intervention effects, all favoring the intervention group, were observed at 6-months for change in weight (-1.35 kg, 95% confidence interval (CI): -2.24, -0.46, P=.003), weekly moderate physical activity sessions (0.56 sessions/week, 95% CI: 0.15, 0.96, P=.008) and accelerometer-assessed MVPA (24.16 minutes/week, 95% CI: 5.07, 43.25, P=.007). Waist circumference, other physical activity outcomes and dietary outcomes, did not differ significantly between groups. CONCLUSIONS: The GHSH extended care intervention led to significantly better anthropometric and physical activity outcomes than standard practice (no contact). This evidence is useful for scaling up the delivery of GHSH as standard practice following the population-level telephone coaching program.